Pregnant women’s knowledge about pregnancy gingivitis and oral health related to quality of life at Bagor Health Center - Widodorini, Trining; Ardiana, Agrisca Salvabella (Faculty of Dental Medicine Universitas Airlangga, 2025)
Background: The formation of biofilm in plaque at the gingival border and the inflammatory reaction to bacteria create gingivitis, an inflammatory reaction of the gingiva. Due to increases in the hormones progesterone and estrogen, pregnancy is a physiological process that might result in physical or psychological changes. Many oral and dental health issues have an impact on pregnant women’s quality of life. Purpose: The study’s goal was to ascertain how pregnant women’s quality of life was impacted by their awareness and knowledge about pregnancy gingivitis and dental health maintenance. Methods: An analytical observational study was used. Total sampling is the method used for sampling. Utilize a questionnaire to assess understanding, and use the Modified Gingival Index (MGI) to assess the gingivitis score. Multiple linear regression was utilized after the Spearman test in data analysis. Results: The findings indicated a relationship between pregnant women’s quality of life and their level of awareness regarding maintaining oral health and pregnancy gingivitis. Inside has a detrimental coefficient value of -1.202, which means that pregnant women’s knowledge increases with decreasing quality-of-life scores, which reflect a good quality of life. A positive coefficient (2.717) is substantially influenced by gingival state, indicating that a lower level of inflammation corresponds to a higher quality of life. Conclusion: Pregnant women’s quality of life is influenced by their level of awareness and knowledge about pregnancy gingivitis and maintaining their oral health. Pregnant women’s quality of life is directly correlated with their ability to maintain oral health.